Incremento del parque automotor y su incidencia socio-económica en los taxistas, cantón Quevedo, periodo 2009-2013. - Panta Plúas, Tanya Narcisa (2015)
Quevedo in Canton taxi cooperatives are engaged in the provision of internal mobility in the city and beyond. Cotur Cooperative Cooperative Alliance, Cooperative San Camilo, Cooperative Nicolas Diaz Infante, King and Cooperative Cooperative Group 6, with a total population of 592 taxis: federated organizations like stand. The 53.22% of the drivers agreed that the new traffic law affects them your income, so that the driver prefers 60.09% manage their own units to reduce operating costs and improve their profits, the cars are working as taxi longer life to six years while the 93.56% about the lack of assistance from the financial system and low income has decided not to replace their units Through this investigation it was known that for 49.79% of the members of taxi cooperatives, local financial system has not contributed to the renewal of vehicle units. The 81.12% exposed through the survey that the new traffic law is not conducive to the taxismo sector, as their sentences and the value of infringements are very hard, to a point to ensure that they would be treated as criminals, which is why to 68.87%, agrees that all changes have impact on their economic and social situation. The established punishment, imprisonment under the 37.34% says it should not exist because this penalty does not correspond to the reality of taxismo. The new Traffic Law, Land Transport and Road Safety if social and economic impact in the area of taxismo, as instructed by 93.56%, affecting development and family growth, due to a drop in revenue and the reduction in profits causing serious monetary difficulties, as stated by the 68.67%. We must add to the above, the economic complications caused by the growth of the informal taxismo, which has not been effectively controlled by transit authorities and spare parts, reducing growth prospects and family development.